Energy efficient lighter weight aluminium matrix composite automotive brake motor - Maleque, Md. Abdul; Adebisi, Adetayo A. (2011)
With 75 percent of fuel consumption relating directly to vehicle weight, potential weight reductions that can result in improved performance ratio and reduce CO2 emissions stimulate the application of lightweight materials. The substitution of aluminium matrix composite (AMC) for structural component of brake rotor is quite effective in lightening, energy efficiency and hence mitigation of global warming. Mathematical models are used to evaluate the influence of light weight material on energy and the environment. This study attempts to predict the effect of weight reduction on energy consumption and CO2 emissions by replacing conventional materials for light weight AMC. The study found that a weight savings of 50 to 60% from the AMC brake rotor can translate to an energy savings of 16-18% in energy usage and hence reduction in CO2 emission in the environment. This study will facilitate a cleaner and healthier environment for human life in the society.